Hubungan Beban Kerja dan Stres Kerja dengan Kinerja Perawat di IGD RSUD Aloei Saboe - Zulkifli Walangadi; Azharatul Jannah; Nurfalia Harfah; Andi Nurul Azizah (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Nurse performance is a key indicator of healthcare quality and patient safety, particularly in Emergency Departments (ED) where workload demands are high. This study aimed to analyze the relationship between workload and job stress with nurse performance in the ED of Prof. Dr. H. Aloei Saboe Hospital. An analytical observational study with a cross-sectional design was conducted involving all 45 ED nurses selected through total sampling. Data were collected using structured questionnaires measuring workload, job stress, and nurse performance, and were analyzed using Spearman’s rank correlation test. Results showed that the majority of nurses experienced high workload (64.44%) and high job stress (53.33%). Statistical analysis revealed a significant negative correlation between workload and nurse performance (p = 0.002; r = -0.448) as well as between job stress and nurse performance (p = 0.001; r = -0.485), both with moderate correlation strength. These findings indicate that higher workload and stress levels are associated with lower nurse performance. The study highlights the need for comprehensive interventions, including optimizing nurse-patient ratios, improving workflow, providing psychosocial support, and implementing stress management programs to maintain nurse performance and service quality in high-pressure ED environments.